Study of Risk Factors Associated with Myopia in Medical Students: A Case-Control Study - Jamila Bibi, Haddaya Umar , Ayesha Azhar , Ammarah Tariq , Muhammad Rizwan Khan, Faud Ahmed Khan Niazi , Jamila Bibi, Haddaya Umar , Ayesha Azhar , Ammarah Tariq , Muhammad Rizwan Khan, Faud Ahmed Khan Niazi (Journal of Rawalpindi Medical College, 2021)
Background: Myopia has emerged as a serious vision-threatening disease globally. Due to its increasing prevalence in the last few decades, it is now considered that along with genetics, environmental and lifestyle factors are also playing some role in the development of myopia. Thus, this study was planned to evaluate the effects of various risk factors in the development and progression of myopia by comparing them with people without myopia. Materials and Methods: A case-control study was conducted on 330 medical students (males=140 and females=190) of a public institute from April to September 2019. Cases include students who were diagnosed with myopia and wear glasses or contact lenses for it. Whereas controls were the students without any visual defect. Data was collected through non-probability convenience sampling from participants between 18 to 25 years from all five years of MBBS. Those with vision defects other than myopia, like hypermetropia, keratoconus, glaucoma, etc., were excluded. Data were entered and analyzed using Statistical Package for Social Sciences (SPSS) version 25 by applying the non-parametric tests and descriptive statistics. Results: Among 330 participants, 185 (56%) had myopia, which increased rapidly between the age of 15 to 20 years in the majority (58.4%) of them. 52.5 % of myopics had a positive family history of myopia. Males were less likely to develop myopia than females (OR=0.65). There was no statistically significant difference in sleeping hours (p-value=0.46), screen exposure time (p-value=0.78) or study hours (p-value=0.15) between myopics and non-myopics. Both groups often take breaks during the study. However, non-myopics were significantly more physically active than myopics (p-value=0.025), which shows that low physical activity is associated with the development of myopia. Conclusion: There is not any significant effect of sleeping hours, screen exposure time, study hours, or breaks during the study on myopia. Myopia is more prevalent in people with a family history of myopia, females, and those with little physical activity.